Immunodeficiency, centromeric region instability, facial anomalies syndrome (ICF) - Jackson Kelly (Orphanet Journal of Rare Diseases, 2006)
Abstract The Immunodeficiency, Centromeric region instability, Facial anomalies syndrome (ICF) is a rare autosomal recessive disease described in about 50 patients worldwide and characterized by immunodeficiency, although B cells are present, and by characteristic rearrangements in the vicinity of the centromeres (the juxtacentromeric heterochromatin) of chromosomes 1 and 16 and sometimes 9. Other variable symptoms of this probably under-diagnosed syndrome include mild facial dysmorphism, growth retardation, failure to thrive, and psychomotor retardation. Serum levels of IgG, IgM, IgE, and/or IgA are low, although the type of immunoglobulin deficiency is variable. Recurrent infections are the presenting symptom, usually in early childhood. ICF always involves limited hypomethylation of DNA and often arises from mutations in one of the DNA methyltransferase genes (DNMT3B). Much of this DNA hypomethylation is in 1qh, 9qh, and 16qh, regions that are the site of whole-arm deletions, chromatid and chromosome breaks, stretching (decondensation), and multiradial chromosome junctions in mitogen-stimulated lymphocytes. By an unknown mechanism, the DNMT3B deficiency that causes ICF interferes with lymphogenesis (at a step after class switching) or lymphocyte activation. With the identification of DNMT3B as the affected gene in a majority of ICF patients, prenatal diagnosis of ICF is possible. However, given the variety of DNMT3B mutations, a first-degree affected relative should first have both alleles of this gene sequenced. Treatment almost always includes regular infusions of immunoglobulins, mostly intravenously. Recently, bone marrow transplantation has been tried.